Bifidobacterium longum W11: Uniqueness and individual or combined clinical use in association with rifaximin. (April 2021) - Di Pierro, Francesco; Pane, Marco
Summary: Backgrounds & aims: Strains belonging to bifidobacteria have been documented as being helpful in adults with intestinal dysbiosis conditions, like those related to irritable bowel syndrome (IBS). This review aims to present the most relevant evidence regarding the efficacy of Bifidobacterium longum W11, a Bifidobacterium used in clinical settings for conditions such as IBS and inflammatory bowel disease. Methods: The following electronic databases were systematically searched up to August 2020: MEDLINE (via PubMed), EMBASE, Cochrane Central Database of Controlled Trials (via CENTRAL), Google Scholar, and Clinicaltrials.gov. Results: Data arising from pooled analysis, 7 in vitro /pharmacological studies, 7 clinical trials including 1 randomized, double-blind and placebo-controlled, showed that the probiotic strain B. longum W11 has been extensively studied for its efficacy in subjects with IBS with constipation, leading to a significant reduction in symptoms. In particular, its role in alleviating constipation was also confirmed in subjects for whom a low-calorie weight-loss diet led to the slowing down of gut motility. The probiotic characteristics of B . longum W11 were further demonstrated in the treatment of minimal hepatic encephalopathy and hepatic disease. The most remarkable trait of B . longum W11 is its non-transmissible antibiotic resistance, due to a nucleotide polymorphism mutation in the rpoB gene, making it resistant to antibiotics of the rifampicin group, including rifaximin. The co-administration of B . longum W11 and rifaximin in patients with symptomatic uncomplicated diverticular disease brought about a further significant improvement in the clinical condition compared to patients treated with rifaximin alone. B . longum W11 is a probiotic which could synergize with rifaximin as an adjuvant to antibiotic treatment. Conclusions: Taken altogether these findings demonstrate the clinical role of the strain W11 both in some functional and in some inflammatory bowel diseases.